Ways of using fiction texts in French language teaching - Davronova , Zulfiya (The Lingua Spectrum, 2025)
The article aims to present the typology of texts to be studied in the course of French language. The relevance of the research is due to the insufficient development of a general typology of texts, the variability of the composition of typologies offered by French-speaking linguists and methodologists, as well as the terminological disorder of the names of the types of texts included in them. The article deals with the main typologies of texts, developed in French linguistics, then with the typologies based on them, used in French lingua-didactics. The methods of observation, comparison, description, interpretation, analysis, synthesis and typology were used in the study. The practical value of the study lies in the possibility of applying the developed typology of texts in teaching French language at different levels and stages of learning.